Ocular preservation with neoadjuvant vismodegib in patients with locally advanced periocular basal cell carcinoma - Sagiv, Oded; Nagarajan, Priyadharsini; Ferrarotto, Renata; Kandl, Thomas J; Thakar, Sudip D; Glisson, Bonnie S; Altan, Mehmet; Esmaeli, Bita (British journal of ophthalmology, 2019)
Locally advanced (T4 per American Joint Committee on Cancer (AJCC) 8th edition) periocular basal cell carcinoma (BCC) can lead to loss of the eye. We report the neoadjuvant use of vismodegib followed by surgery in patients with such lesions with eye preservation as primary goal. This retrospective interventional study includes all patients with a T4 periocular BCC (per 8th edition AJCC for eyelid carcinoma) treated by the senior author between 2013 and 2017 with neoadjuvant vismodegib prior to definitive surgery. Eight patients had a T4 tumour. Six patients presented with recurrent disease. Indications for neoadjuvant treatment were an unresectable tumour in one patient, an attempt to avoid an orbital exenteration in six patients and an attempt to avoid disfiguring facial surgery in one patient. Patients were treated for a median of 14 months (range: 4-36 months). All patients underwent an eye-sparing surgery following neoadjuvant vismodegib and all final surgical margins were negative for tumour. Five patients had a complete response to vismodegib with no microscopic residual BCC found during surgery; three patients had a significant partial response with residual tumour found on pathology. At last follow-up, a mean of 18 (range: 6-43) months after surgery, all patients were off-vismodegib and alive without evidence of disease. Neoadjuvant vismodegib for locally advanced (T4) periocular BCC enabled an eye-sparing surgery in all patients in our cohort. Prolonged treatment was well tolerated by most patients. Over half of patients achieved a complete response with no residual microscopic disease. Careful long-term follow-up is needed to confirm long-term disease-free survival.